Pets at work: Integrating pet-friendly initiatives into human resources for enhanced workplace harmony - Junça Silva, A.; Galrito, M. (BMC Psychology, 2024)
Aims The representation of companion animals, or pets, has been changing recently. Research concerning how pets influence employees’ work-related well-being has also started to take its first steps. This research aimed to analyze (1) how managers perceive pet-friendly practices and their main effects at work, and (2) the impact of such practices on employees’ well-being and work engagement. Relying on the social exchange perspective and the self-determination theory it was hypothesized that pet-friendly practices would positively influence employees’ well-being and work engagement by satisfying their three basic needs (autonomy, competence, and relatedness). Methodology Two studies with mixed methods were conducted. The first and exploratory study resorted to semi-structured interviews with six managers. The second was a two-wave study conducted with a large sample of workers (N = 379). Results The first study highlighted the primary advantages and disadvantages of pet-friendly practices, along with the various obstacles and limitations, and proposed managerial strategies to overcome them. Managers generally expressed interest and enthusiasm about the topic but also pointed out challenges in implementing a pet-friendly strategy due to the limited number of empirical studies demonstrating its benefits. The second study’s findings indicated that pet-friendly practices positively impacted employees' work engagement and well-being by fulfilling their needs for competence, autonomy, and relatedness. Originality Overall, Portugal is seen as having a conservative culture, which slows the dissemination and implementation of these measures. To overcome these challenges, several managerial recommendations have been proposed. Raising awareness and fostering discussion on the topic are crucial steps toward integrating pet-friendly policies into human resources management.